ANALISIS PERSEPSI KONSUMEN TERHADAP BAURAN PEMASARAN PRODUK KERIPIK NANAS DI KUALA NENAS KOTA PEKANBARU - Et, Elfa Azani; Yusri, Jum'atri; Restuhadi, Fajar (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
This study aims to determine consumer characteristics, analyze consumer decision-making processes in purchasing, evaluate the importance and performance of marketing mix attributes, and determine consumer satisfaction with the marketing mix of pineapple chips produced by Kualu Nenas Village. Sampling uses Purposive sampling method. Data were analyzed using descriptive methods, Importance Performance Analysis, Customer Satisfaction Index. The results showed the consumer characteristics of pineapple chips in Pekanbaru City as follows: 73% female, the largest age group 26-31 years, 48% employment as private employees, 50% of undergraduate education, income above 4,500,000. The purpose of buying pineapple chips is for souvenirs because the food is typical of Riau with good taste. Only 44% of consumers seek information about brands before buying. The reason for choosing a place of purchase is the condition of a place that is comfortable and easily accessible. The attributes of pineapple chip that must be improved by the manufacturer are the attributes of the tester. The attributes that must be maintained so that consumers continue to buy pineapple chips are product taste, product color, health office permit, expiration date, halal label, hygiene quality, packaging contents, form integrity, affordability, accessible location, signpost name shop, visibility and comfort of the place. Attributes that according to consumers are not too important and their performance is low are information on the composition of raw materials, packaging design, competitive prices, product signboards and sales promotions. Attributes that have performed well but are not considered important are brand, product durability and store popularity. Consumer satisfaction of 82.03% means that consumers are satisfied.